Infusing Indigenous Knowledge and Epistemologies: Learning From Teachers in Northern Aboriginal Head Start Classrooms - Peterson, Shelley; Jang, Soon; San Miguel, Jayson; Styres, Sandra; Madsen, Audrey (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2018)
Five Aboriginal Head Start early childhood educators from a northern Canadian community participated in interviews for the purpose of informing non-Indigenous teachers’ classroom teaching. Their observations and experiences highlight the importance of learning from and on the land alongside family members, and of family stability and showing acceptance of all children. Additionally, participants talked of the impact of residential schools on their families in terms of loss of their Indigenous language, and their attempts to learn and to teach the children in their classrooms the Indigenous languages and teachings.